De la teoría a la práctica: Identificación de situaciones de problemas a partir de la práctica pedagógica (Educational Perspectives Magazine (REPED), 2022)
Initial teacher formation involves a series of challenges, perhaps one of the biggest is associated with the need for this, is linked to real-world environments inwhich they are about to perform at future professionals. Faced with this challenge the didactic options are varied, in this context reveáis a joint educational experience associated with differential educational training at the Universidad Católica de Temuco, which sought to link theoretical leaming with practice in experience under the context of curriculum renewal that lives the University and the Faculty of Education in particular and that is associated with a curricular model in which the axes is competency-based competence.
Keywords: Collaboration, Joint Teaching, Competence, Reflective Cycle, Curriculum Theory, Educational Workshop